Lithium storage in structurally tunable carbon anode derived from sustainable source. (September 2017) - Lim, Daw Gen; Kim, Kyungho; Razdan, Mayuri; Diaz, Rosa; Osswald, Sebastian; Pol, Vilas G.
Abstract: A meticulous solid state chemistry approach has been developed for the synthesis of carbon anode from a sustainable source. The reaction mechanism of carbon formation during pyrolysis of sustainable feed-stock was studied in situ by employing Raman microspectroscopy. No Raman spectral changes observed below 160 °C (thermally stable precursor) followed by color change, however above 280 °C characteristic D and G bands of graphitic carbon are recorded. Derived carbon particles exhibited high specific surface area with low structural ordering (active carbons) to low specific surface area with high graphitic ordering as a function of increasing reaction temperature. Carbons synthesized at 600 °C demonstrated enhanced reversible lithiation capacity (390 mAh g −1 ), high charge-discharge rate capability, and stable cycle life. On the contrary, carbons synthesized at higher temperatures (>1200 °C) produced more graphite-like structure yielding longer specific capacity retention with lower reversible capacity. Graphical abstract: